2019
DOI: 10.1021/acs.chemmater.8b05073
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Triblock Janus Nanoparticles: Synthesis and Self-Assembly

Abstract: Multiblock Janus nanoparticles (JNPs) are anisotropic particles composed of different blocks/lobes with distinct physicochemical properties. The ultimate goal is to obtain JNPs that carry two or more contrasting bulk and surface properties on different parts of the same particle. JNPs are promising candidates for various applications, such as building blocks for self-assembly and multifunctional materials. Here, we report the chemical synthesis of a special type of “versatile” triblock JNPs, which contain thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…76 Authors then showed the enhanced diffusion of the GOx/Ct Janus nanomotors in the biologic medium in the presence of various concentrations of glucose and use solely the MSD analysis of the particles' motion to prove enhanced diffusion of the Janus particles in the presence of glucose. Futher examples of Janus nanomotors include light-activated nanoparticles, 71,74 novel carriers as MOFs, 67 noble-metal composite nanoparticles, 75,78 bio-mimetic nanoparticles, 46,70 porous-silica based nanomotors, 80,60 polymeric capsules, 73 and cup-like structures. 43,68,79 Hollow Nanorobots Another type of nanomotor that has been extensively studied is the hollow particle with catalyst loaded inside.…”
Section: Sphere Dimersmentioning
confidence: 99%
See 1 more Smart Citation
“…76 Authors then showed the enhanced diffusion of the GOx/Ct Janus nanomotors in the biologic medium in the presence of various concentrations of glucose and use solely the MSD analysis of the particles' motion to prove enhanced diffusion of the Janus particles in the presence of glucose. Futher examples of Janus nanomotors include light-activated nanoparticles, 71,74 novel carriers as MOFs, 67 noble-metal composite nanoparticles, 75,78 bio-mimetic nanoparticles, 46,70 porous-silica based nanomotors, 80,60 polymeric capsules, 73 and cup-like structures. 43,68,79 Hollow Nanorobots Another type of nanomotor that has been extensively studied is the hollow particle with catalyst loaded inside.…”
Section: Sphere Dimersmentioning
confidence: 99%
“…The rules governing the engineered self-assembly of nanoparticles could also serve as strategies for reversible swarm behavior in large sets of individual nanorobots. 78,99…”
Section: Applications Of Nanomachinesmentioning
confidence: 99%
“…JNPs consisting of two or more separate polymeric components have been extensively reported. , Polymeric components possess greater flexibility, customizable functionality, higher stability, and biocompatibility . Fickle structures have also been proposed, such as nanobowls, nanohats, nanocups, and nanocages. , Synthetic strategies for more representative polymeric JNPs are categorized (but not limited) into four main types: self-assembly strategy, phase separation strategy, seed-mediated polymerization synthesis strategy, and microfluidic synthesis strategy.…”
Section: Synthetic Strategies Of Polymeric Composite Jnpsmentioning
confidence: 99%
“…It is of importance that nanoparticles (NPs) with an asymmetric heterostructural junction at the micro/nanoscale provide many interesting properties, which are not approachable in symmetric or homogeneous nanostructures. For example, in the case of Fe 3 O 4 -Au JNPs, one part of Fe 3 O 4 NPs showed magnetic properties, whereas the other part of Au NPs possessed a localized surface plasmon resonance (LSPR) property. The Janus structure allowed the combination of Fe 3 O 4 with Au, thereby providing a different surface polarity or interior chemistry compared to the corresponding single component, and further exhibited enhanced biomedical performance. , Over the past decades, JNPs have promptly extended from particles with two sides of opposite polarity to materials possessing various regions that have diverse compositions, morphologies, and properties. JNPs have also exhibited superior performance in diverse of areas, for example, self-motile micro/nanomotors, compared to other NPs, including homogeneous sphere, yolk/shell nanostructures, core/shell nanostructures, hollow structures, etc.…”
mentioning
confidence: 99%
“…The asymmetric and dual-compartmentalized structures of JPs offer compelling access to various applications, including particulate surfactants, self-mobile particles, electric/magnetic field-driving devices, , and materials for bio/life science. , Progress in nanotechnology has made it possible to construct numerous JPs either by breaking the symmetry of existing particles or directly synthesizing smaller components into single particles. Special methodologies have been developed to effectively fabricate JPs, such as subsequent surface modification, microfluidics, self-assembly of block copolymers, seeded polymerization, electrified cojetting, and microphase separation in the confined volume. The push for further development is now facing new challenges of fabricating triphasic particles, which consist of three different parts with distinct features in the same particle. The triphasic particles have been successfully constructed in few cases, using colloid lithography, , seeded polymerization, microfluidics, , and electrified cojetting. , Among them, the in situ photoinitiated radical polymerization in microfluidics and seeded emulsion polymerization were used to synthesize ternary particles and triblock nanoparticles. , The colloidal spheres with three or more different zones were prepared through colloid lithography for the directed self-assembly. , In the processes of electrified jetting and electrohydrodynamic cospinning, a polymer solution containing three different dyes or fluorescent nanobeads was employed to demonstrate the multicompartmentalized effects. However, a method via microphase separation in a confined volume, a feasible way to obtain discrete domains of different materials under an internal driving force, has not been adopted for the construction of ternary particles yet.…”
Section: Introductionmentioning
confidence: 99%